The Modelling Tariff of Solid Waste Management Retributions for Malang City - Maisyah, Siti; Adi, Trijoko Wahyu; Warmadewanthi, I.D.A.A (Institut Teknologi Sepuluh Nopember, 2017)
Cost of solid waste management, in Malang City, can not be covered by retribution; therefore government has to subsidized. Solid waste management expense consist of TPS (temporary collection location/Tempat penampungan sementara) investment, operational/maintenance of TPS, wipe of general facility, transport from TPS to landfill and landfill treatment. This study suggest tariff retribution calculation model of solid waste mangement at Malang City. The proposed model integrate 2 method, they are Activity Based Costing (ABC) system and building type. Activity Based Costing (ABC) system is used to gather cost of waste management. While building type is used to put cost upon tariff retribution of waste management at Malang City. The early stages was to identify any activities that generate expenses in waste management. The next phase is determining the cost driver from each activites. The last step is devide amount retribution based on building type. The result from this study show that cost of street sweeping is Rp. 6.275,35/km; cost of transporting solid waste is Rp. 96.832,40/trip and cost of landfill treatment is Rp. 6.275,35/m3. After that, calculate based on solid waste generated each type building.